Moderate-severe aortic arch calcification and high serum alkaline phosphatase co-modify the risk of cardiovascular events and mortality among chronic hemodialysis patients - Cheng-Hao Chang; Hung-Hsiang Liou; Chung-Kuan Wu (Renal Failure)
Background Patients with end-stage kidney disease undergoing chronic hemodialysis (HD) have an unparalleled risk of vascular calcification (VC) and high alkaline phosphatase (Alk-P) levels. However, whether VC contributed to the cardiovascular risk modified by serum Alk-P levels was not addressed in the population.Methods A retrospective cohort study was conducted on chronic HD patients, between October 1 and December 31, 2018, with aortic arch calcification (AoAC) scores and serum Alk-P levels. Patients were categorized into four groups: non-to-mild AoAC/low Alk-P, non-to-mild AoAC/high Alk-P, moderate-to-severe AoAC/low Alk-P, and moderate-to-severe AoAC/high Alk-P. The Cox proportional hazard model and Kaplan–Meier analysis were used to evaluate the risks of major adverse cardiovascular effects (MACEs) and cardiovascular and all-cause mortality after multivariate adjustment.Results Among 376 chronic HD patients recruited, 125 (33%) had non-to-mild AoAC/low Alk-P, 76 (20%) had non-to-mild AoAC/high Alk-P, 89 (24%) had moderate-to-severe AoAC/low Alk-P, and 86 (23%) had moderate-to-severe AoAC/high Alk-P. After 3 years of follow-up, patients with coexisting moderate-to-severe AoAC and high Alk-P had a higher risk of MACEs (aHR 1.76; 95% CI 1.06–2.92), and cardiovascular (aHR 2.49; 95% CI 1.21–5.11) and all-cause mortality (aHR 2.67; 95% CI 1.39–5.13) compared to those with non-to-mild AoAC/low Alk-P even after adjustments for significant clinical variables.Conclusions In chronic HD patients, moderate to severe AoAC co-existed with high Alk-P levels and enhanced the risk of MACEs and cardiovascular and all-cause mortality. Interventions to attenuate these risk factors simultaneously should be emphasized in this population.